A symmetric experimental study of the interaction between regular waves and a pontoon breakwater with novel fin attachments - Lyu, Xiangcheng; Yang, Yifeng; Mi, Chenhao; Tang, Chi Man; Adeboye, Lukman; Farhan, Mohamed; Collins, Stan; Ou, Binjian; Wong, Anson; Duffy, John Gordon; Huang, Luofeng (MDPI, 2024)
Floating breakwaters are widely applied on the ocean water surface to protect human infrastructure from the destructive power of waves. This study designs and investigates the performance of a novel symmetric-pontoon floating breakwater with a symmetric pair of hydrofoils. Based at the Cranfield Ocean Systems Laboratory, the system was constructed and tested in various wave conditions using different fin configurations. The floating structure was anchored using a symmetric four-point mooring system. The tested waves were regular and symmetric perpendicular to the propagating direction. Key parameters, including the attenuated wave amplitude, motions of the breakwater, and the mooring forces, were measured. The wave parameters utilised for testing covered 1.61–5.42 relative wavelength to structural length, with wave heights of 3 cm and 5 cm. Results showed the 90° fin configuration can reduce wave transmission by up to 74%, with the lowest mooring forces at 3.05 relative wavelength, enhancing the performance of wave energy dissipation and structural seakeeping. At 90° setup, the mooring force was lowest at 2.41 relative wavelength. This research can inform novel designs of breakwaters to improve protection abilities for coastal cities and offshore infrastructures, especially renewable energy systems.
Keywords: floating breakwater; wave tank experiment; fin attachment; wave attenuation; mooring forces